2017
DOI: 10.1177/0954008317698548
|View full text |Cite
|
Sign up to set email alerts
|

Highly transparent and soluble polyimides with synergistic effects of pyridine and cyclohexane

Abstract: In order to prepare novel polyimides (PI) with high transparency and solubility in common solvents, three diamine monomers containing pyridine or methyl-substituted pyridine and cyclohexane, 1,1′-bis[4-(5-amino-2-pyridinoxy)phenyl]cyclohexane (IIIa), 1,1′-bis[4-(5-amino-3-methyl-2-pyridinoxy)phenyl]cyclohexane (IIIb), and 1,1′-bis[4-(5-amino-2-methyl-6-pyridinoxy)phenyl]cyclohexane (IIIc), were synthesized and characterized. The diamine monomer (IIIa) was subsequently polymerized with 3,3′,4,4′-oxydiphthalic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Yao et al 107 polymerized 1,1′‐bis[4‐(5‐amino‐2‐pyridinoxy)phenyl]cyclohexane, 1,1′‐bis[4‐(5‐amino‐3‐methyl‐2pyridinoxy)phenyl]cyclohexane, and 1,1′‐bis[4‐(5‐amino‐2‐methyl‐6‐pyridinoxy)phenyl]cyclohexane (III a ‐III c in Figure 6a), three diamine monomers containing alicyclic structures, with 6FDA and other dianhydrides, respectively, to obtain a series of highly transparent PI films (~30 μm). Due to the introduction of pendant cyclohexane and pyridine with high refractive index, the λ 0 of these PI films are between 345 and 359 nm, and T 500 are as high as 94%–97%.…”
Section: Highly Transparent Pi Filmsmentioning
confidence: 99%
“…Yao et al 107 polymerized 1,1′‐bis[4‐(5‐amino‐2‐pyridinoxy)phenyl]cyclohexane, 1,1′‐bis[4‐(5‐amino‐3‐methyl‐2pyridinoxy)phenyl]cyclohexane, and 1,1′‐bis[4‐(5‐amino‐2‐methyl‐6‐pyridinoxy)phenyl]cyclohexane (III a ‐III c in Figure 6a), three diamine monomers containing alicyclic structures, with 6FDA and other dianhydrides, respectively, to obtain a series of highly transparent PI films (~30 μm). Due to the introduction of pendant cyclohexane and pyridine with high refractive index, the λ 0 of these PI films are between 345 and 359 nm, and T 500 are as high as 94%–97%.…”
Section: Highly Transparent Pi Filmsmentioning
confidence: 99%
“…The formation of CTCs can be inhibited by introducing strong electronegative groups (such as −CF 3 ), alicyclic structures, and inorganic particles , into PI. However, these changes also reduce the linearity and rigidity of the polymer chains, resulting in poor thermal and mechanical properties of PI.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Fortunately, it is considered an effective way that incorporating bulky pendant groups into PIs to improve their processability and transparency, and meanwhile maintain their high thermal stability. [31][32][33][34] In previous work, we found that the introduction of cyclohexyl and tert-butyl groups into PIs was able to increase their T g s, solubility and transparency, 34 but the cost was relatively high. In order to decrease the cost and further enhance the T g s of PIs, we intend to use methyl instead of tert-butyl.…”
Section: Introductionmentioning
confidence: 99%